Correlation of matrix metalloproteinase (MMP)-1, -2, -3, and -9 expressions with demographic and radiological features in primary lumbar intervertebral disc disease. (July 2017) - Basaran, Recep; Senol, Mehmet; Ozkanli, Seyma; Efendioglu, Mustafa; Kaner, Tuncay
Highlights: MMP-1, -2, -3, and -9 expressions was examined on primary lumbar disk herniation. MMP-1 and -2 are increased with age. The higher MMP-9 expression is the higher MRI grading. Abstract: Degeneration of IVD is a progressive and irreversible process and can be evaluated with immunohistochemical examination or radiological grading. MMPs are a family of proteolytic enzymes and involved in the degradation of the matrix components of the IVD. We aimed to compare MMP-1, -2, -3, and -9 expressions with demographic features, visual analogue scale (VAS), Oswestry Disability Index (ODI) and radiological (MRI) grades. The study involved 60 participants. We recorded data about age, complaint, radiological imaging, expression levels of MMP-1, -2, -3, and -9, ODI and VAS for back pain retrospectively. Intervertebral disc degeneration was graded on a 0–5 scale according to the Pfirrmann classification. As a result of the study, the median age was 52.09 ± 12.74 years. There were statistical significances between age and MMP-1, and MMP-2. There was a close correlation between grade and MMP-9. We found correlation between the VAS and the MMP-9 expression. In addition, there was relationship between expression of MMP-2 and MMP-1, MMP-3, MMP-9. In conclusion, the expressions of MMP-1 and -2 are increased with aging. There was no relationship between radiological evaluation of IVDD and aging. Increased expression of MMPs affected IVDD positively. The relationship with MMPs is not explained. This study adds to our understanding of the interaction between MMPs and IVDD.